Capital adequacy and maturity matching status of Hungarian district heating companies - Süveges Gábor; Bozsik Sándor; Szemán Judit (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. In Hungary, district heating services cover 650,000 households (more than 2 million residential consumers) and a large number of public and industrial consumers. The capital adequacy and maturity matching status of Hungarian district heating companies is important because it has an impact on their ability to cope with economic crises. The financial situation of a company or a group of companies in an industry is analyzed by means of ratios of the financing structure. This paper examines the capital adequacy and maturity matching of district heating companies in Hungary using disaggregated annual reports. The methodology is based on report analysis, using data from the accounts of the companies providing district heat services in Hungary -72 companies make up the sample-. The analyses provide a comprehensive picture of the capital adequacy and coverage ratios of the district heating companies and show that the maturity matching principle is implemented differently for the different profiles of district heating companies. To achieve the research objectives, vertical and horizontal analyses were needed. Based on the accounting unbundled reports, it can be stated that the structure of owner's equity and liabilities of district heating companies is significantly influenced by the sales size and ownership structure. The principle of maturity consistency is implemented in different ways. This study has analyzed the characteristics of the owner's equity and liabilities of district heating companies - through horizontal and vertical studies - focusing on two main indicators. The largest share of the owner's equity and liabilities of district heating companies is represented by equity, with an average value of more than 50% each year. On average, the companies with a district heating profile, the largest sales size, own heat production, and the majority of the companies that are not privately owned are characterized by higher coverage.

Magyarországon a távhőszolgáltatás 650 000 háztartást (több mint 2 millió hazai fogyasztót), valamint nagyszámú lakossági és ipari fogyasztót érint. A magyar távhőszolgáltatók számára fontos a tőke megfelelősége, a forrásbevonás ütemezése és felhasználásának megfelelő időzítése, hisz befolyásolja a gazdasági válságokkal való megküzdési képességet. A finanszírozási szerkezet mutatói segítségével elemzésre kerül az iparágban egy vállalat vagy vállalatcsoport pénzügyi helyzete. Jelen cikk a magyarországi távhőszolgáltatók tőkéjének megfelelőségét és adósságlejáratát vizsgálja nem összevont éves jelentések segítségével. A módszertan a Magyarországon távhőszolgáltatást nyújtó társaságok beszámolóiból származó adatok felhasználásával készült jelentések elemzésén alapul - a mintát 72 cég alkotja. Az elemzés teljes képet ad a távhőszolgáltató társaságok tőkemegfelelési és fedezettségi mutatóiról, és azt mutatja, hogy az adósságtörlesztési feltételek összeegyeztetésének elve a távhőszolgáltatók különböző profiljainál eltérően valósul meg. A tanulmány céljainak elérése érdekében vertikális és horizontális elemzéseket végeztünk. A számviteli kimutatások alapján megállapítható, hogy a hőszolgáltató társaságok saját tőkéjének és forrásainak szerkezetét jelentősen befolyásolja az árbevétel mértéke és a tulajdonosi szerkezet. Az eszköz- és forrásfeltételek megfeleltetésének elvét különböző módokon valósítják meg. Jelen tanulmány horizontális és vertikális tanulmányozáson keresztül elemzi a távhőszolgáltató társaságok tőke- és kötelezettségi mutatóit, két fő mutatóra fókuszálva. A hőszolgáltató társaságok saját tőkéjének és kötelezettségeinek legnagyobb hányadát az évente átlagban 50%-os értéket meghaladó saját tőke teszi ki. Átlagosan a központosított hőszolgáltató profillal, legnagyobb értékesítési volumennel, saját hőtermeléssel rendelkező cégekre, valamint a legtöbb nem magánvállalkozásra jellemző a magasabb lefedettség.

Резюме. В Угорщині послуги централізованого опалення охоплюють 650 тис. домогосподарств (понад 2 мільйони побутових споживачів) і велику кількість громадських та промислових споживачів. Достатність капіталу та статус відповідності термінів залучення коштів строкам їх використання для угорських компаній централізованого теплопостачання є важливими, оскільки це впливає на їх здатність справлятися з економічними кризами. Фінансовий стан компанії або групи компаній у галузі аналізується за допомогою показників структури фінансування. У цьому документі розглядається відповідність достатності капіталу та строків погашення боргів компаній централізованого теплопостачання в Угорщині з використанням дезагрегованих річних звітів. Методологія ґрунтується на аналізі звітів із використанням даних з облікових записів компаній, що надають послуги централізованого теплопостачання в Угорщині - 72 компанії складають вибірку. Аналіз дає повну картину достатності капіталу та коефіцієнтів покриття компаній централізованого теплопостачання й показує, що принцип узгодження строків погашення боргових зобов’язань реалізується по-різному для різних профілів компаній централізованого теплопостачання. Для досягнення цілей дослідження здійснено вертикальний і горизонтальний аналізи. Виходячи з бухгалтерської звітності, можна констатувати, що на структуру власного капіталу та зобов’язань теплопостачальних компаній суттєво впливає розмір продажів та структура власності. Принцип узгодженості строків активів і пасивів реалізується по-різному. У цьому дослідженні проаналізовано характеристики власного капіталу та зобов’язань компаній централізованого теплопостачання за допомогою горизонтальних і вертикальних досліджень, зосереджуючись на двох основних показниках. Найбільшу частку власного капіталу та зобов'язань теплопостачальних компаній становить власний капітал із середнім значенням понад 50% щороку. В середньому, компанії з профілем централізованого теплопостачання, найбільшим обсягом продажів, власним виробництвом тепла, а також більшість компаній, які не є приватними, характеризуються вищим рівнем покриття.
Tőke- és lejárati megfelelőség állapota a magyar távhőszolgáltató vállalatoknál
Достатність капіталу та стан відповідності строків погашення в угорських компаніях централізованого теплопостачання
https://aab-economics.kmf.uz.ua/aabe
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010508
Keywords: structure of owner's equity and liabilities; district heating service; report analysis